Surface erosion and underground leakage of yellow soil on slopes in karst regions of southwest China. (28th May 2018) - Dai, Quanhou; Peng, Xudong; Wang, Peijiang; Li, Changlan; Shao, Hongbo
Abstract: Surface erosion and underground leakage loss simultaneously exist on slopes with a double‐layered structure (surface and underground) and have caused rocky desertification in karst regions. Because of the great difficulty of directly determining the underground leakage loss of soil and water, soil erosion processes in this region remain unclear, especially underground leakage loss. The aim of this study was to reveal the plot‐scale characteristics of surface soil erosion and underground leakage loss of yellow soils on karst slopes. Simulated rainfall tests and field runoff plot monitoring were conducted to achieve this aim. We found that surface erosion formed on steep slopes (30°) or at greater rainfall intensities (over 50 mm hr −1 ) and that surface runoff and surface soil loss dominated the total runoff and soil loss on karst slopes at greater rainfall intensities. However, underground leakage loss always occurred at different slopes and rainfall intensities. For small rainfall intensity cases (lower than 80 mm hr −1 ), underground runoff and underground soil leakage loss dominated the total runoff and soil loss and showed an underground runoff ratio of over 90% and an underground soil leakage ratio of over 44%. Rainfall intensity had significant effects on surface runoff depth and surface soil loss rates but an insignificant influence on underground leakage loss. Slope gradient and slope length influenced the runoff yield, and slope degree had a greater effect on the surface soil loss than had slope length. This study improves our understanding of surface erosion and underground leakage loss in karst rocky desertification regions.